Outcomes of sepsis: a new look at old problems - A. Yu. Savochkina; L. R. Pykhova; O. S. Abramovskikh; E. A. Chetvernina; A. E. Poltorak (Медицинская иммунология, 2022)
Infections represent a common health problem in people at any age. Usually, a local reaction develops in response to the infection, and intensive treatment is not required. However, sometimes the response to infection is inadequate and may lead to organ dysfunction; such condition is defined as septic state. The pathophysiology of sepsis is multifactorial, and the immune system is directly involved in development of pathological processes accompanying septic conditions. Dysregulatory disorders in sepsis may be observed, in particular, those affecting immune system and, immediately, innate immunity, which presents the first line of immune defense. Currently, neutrophilic granulocytes are considered important players in development and maintenance of inflammatory processes, which is due to their ability to produce various inflammatory mediators. At the same time, at different stages of pathogenesis, immune factors and mechanisms act both as a generating factors and effectors of damage reactions, as well as the main components of the defense responses. Uncontrolled release of endogenous inflammatory mediators induced by microorganisms, and lack of damagelimiting mechanisms mutually synergize when promoting the organ dysfunction. Hence, dysfunction of the immune system may develop and deepen upon any inappropriate strategy of response to distinct infectious pathogen. The aim of our study was to assess the spectrum of microorganisms, levels of neutrophilic extracellular traps (NVL), PAD4, IL-6, IL-8 and their correlations in the patients with sepsis and septic shock, depending on the outcome of the disease. The study included 44 patients with sepsis and septic shock, and 20 apparently healthy donors. Peripheral blood samples were taken from the ulnar vein serially in dynamics, from the moment of diagnosis to clinical outcome. Microbiological and immunological studies have been carried out. The obtained data were processed with “SPSS Statistic 23.0” software. Development of septic conditions was found to be accompanied by a significant changes in the levels of studied immunological parameters (NLV, IL-6, IL-8 and PAD4). Toxicity of lysosomal enzymes and oxygen metabolites present in neutrophilic extracellular traps leads to endothelial damage, appearance of focal intravascular inflammation, which, along with damaging effects of microorganisms and their toxins, leads to development of organ failure and onset. High burden   of these factors is most likely to cause lethal outcomes.